Anatta (No Self) in Buddhism Through the Lens of Modern Psychology - Bui, Thang Van (International Journal of Social Sciences and English Literature, 2025)
Anatta or selflessness is a core concept in Buddhism. Unlike other religions in the Buddha’s era, Buddhism proposes that the world, including the self, is not impermanent but changes continually. Accepting that the self is an impermanent existence and adherence to the world, as we suppose it is permanent, is the root of suffering. While Buddhism is known as an ancient religion, dated over two thousand years ago, it is still practiced around the world in the present time. This paper discusses the importance of understanding the characteristics of self and the role of self in modern life. Also, to shed light on the alignments of anatta in modern psychology, self-help, supported by positive psychology, is analyzed in a way that explores the nature of anatta. Finally, the paper gives implications of anatta for one to reduce suffering by accepting possible changes in life and to help oneself recover from suffering.